Mechanism of Cell Penetration by Permeabilization of Late Endosomes: Interplay between a Multivalent TAT Peptide and Bis(monoacylglycero)phosphate. Issue 10 (15th October 2020) - Brock, Dakota J.; Kondow-McConaghy, Helena; Allen, Jason; Brkljača, Zlatko; Kustigian, Lauren; Jiang, Mengqiu; Zhang, Junjie; Rye, Hays; Vazdar, Mario; Pellois, Jean-Philippe
Summary: Many cellular delivery reagents enter the cytosolic space of cells by escaping the lumen of endocytic organelles and, more specifically, late endosomes. The mechanisms involved in endosomal membrane permeation remain largely unresolved, which impedes the improvement of delivery agents. Here, we investigate how 3TAT, a branched analog of the cell-penetrating peptide (CPP) TAT, achieves the permeabilization of bilayers containing bis(monoacylglycero)phosphate (BMP), a lipid found in late endosomes. We establish that the peptide does not induce the leakage of individual lipid bilayers. Instead, leakage requires contact between membranes. Peptide-driven bilayer contacts lead to fusion, lipid mixing, and, critically, peptide encapsulation within proximal bilayers. Notably, this encapsulation is a distinctive property of BMP that explains the specificity of CPP's membrane leakage activity. These results therefore support a model of cell penetration that requires both BMP and the vicinity between bilayers, two features unique to BMP-rich and multivesicular late endosomes. Graphical Abstract: Highlights: CPP-mediated leakage of membranes mimicking late endosomes requires bilayer contact The presence and abundance of BMP are primary determinants of leakage CPPs promote leakage by being encapsulated by BMP at contact sites BMP uniquely promotes CPP encapsulation, which leads to escape from late endosomes Abstract : Endosomal membrane translocation requires encapsulation of cationic CPPs between bilayers brought into close contact. The presence and abundance of the anionic lipid BMP are primary determinants of luminal leakage. Molecular dynamic simulations explain this mechanism through peptide-induced BMP spatial disarrangement and inverted micelle formation.